2021
DOI: 10.2478/acta-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Education and Marital Status as Determinants of Job Satisfaction

Abstract: The issue of job satisfaction has been discussed by the researchers and managers of organizations for several decades. There are many different approaches to the issue. Currently, it is possible to find the research dealing with psychological aspects determining the level of job satisfaction, the research analysing the role of satisfaction and work motivation and the research focused on the consequences of job satisfaction and dissatisfaction. This paper describes how the job satisfaction of employees differs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Division/ Organization of employee placement greatly affects employee job satisfaction because it is influenced by several factors such as work culture, coworkers, superiors and how the job matches the employee's abilities. This is supported by previous research conducted by Agustriyana [43] where the employee placement variable has an influence of 69% Uhlir and Rehor [46] who found that people who studied at the university level at the diploma/ graduate level felt they had better job satisfaction than people who did not study at the university level. This is also supported by the opinion of Notoadmodjo [47] which states that the level of education greatly influences a person's level of knowledge which also has an impact on a person in receiving and understanding the information obtained.…”
Section: Discussionsupporting
confidence: 81%
“…Division/ Organization of employee placement greatly affects employee job satisfaction because it is influenced by several factors such as work culture, coworkers, superiors and how the job matches the employee's abilities. This is supported by previous research conducted by Agustriyana [43] where the employee placement variable has an influence of 69% Uhlir and Rehor [46] who found that people who studied at the university level at the diploma/ graduate level felt they had better job satisfaction than people who did not study at the university level. This is also supported by the opinion of Notoadmodjo [47] which states that the level of education greatly influences a person's level of knowledge which also has an impact on a person in receiving and understanding the information obtained.…”
Section: Discussionsupporting
confidence: 81%
“…This empirical study contributed to the body of knowledge on the factors impacting employees' job satisfaction in the context of the Czech Republic. Inspired by the international (Kaiser, 2007;Wilczyńska et al, 2016;Coo et al, 2020) and Czech context unique studies (Franěk et al, 2014;Čábelková et al, 2015;Uhlíř and Řehoř, 2020), the provided findings extend the regional state of the art from the perspective of statistically representative empirical analysis of Czech employees (N=12,699), extracted from the 2017 edition of the European Union Labour Force Survey (EU LFS). This article's novelty is a more complex understanding of the occupational and organizational aspects of job satisfaction.…”
Section: Discussionmentioning
confidence: 66%
“…Also, we addressed some contradictory observations of earlier studies regarding gender. Uhlíř and Řehoř (2020) found no differences in satisfaction between employed men and women, and Lange (2009) observed higher satisfaction among women. In contrast, studies by Franěk et al (2014) and Čábelková et al (2015) observed higher satisfaction among men, which was also the case in the conducted analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation